PENDIDIKAN KESEHATAN TENTANG RUMAH SEHAT COVID-19 BAGI KADER COVID-19 DI DESA BOGOREJO MERAKURAK TUBAN TAHUN 2021 - Hyan Oktodia Basuki; Hanim Nur Faizah; Dyah Pitaloka; Suhartono Suhartono (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
The spread of covid-19 is currently very fast and extensive to the village level. In preventing the spread of covid-19 several task forces have been formed in each village. The task force is responsible for the spread of covid-19 in village areas and provides education on the application of health protocols. Apart from the responsibilities of the task force, several villages have also formed health cadres to help. Health cadres have been provided with education on procedures for the implementation of isolation for families exposed to Covid-19. However, it is still not effective because of the increasing number of cases. The addition creates new problems, related to the standardization of isolation houses in villages that do not meet the criteria of government regulations, one example is the isolation house in the Bogorejo, Merakurak, Tuban. Isolation houses are provided right next to the village office but do not the standards. The reason, activity of providing health education about Covid-19 healthy homes for cadres need to be implemented. This activity aims to broaden the knowledge of health cadres, and the community to seriously pay attention to health protocols to prevent the spread of covid-19 in the area of Bogorejo, Merakurak, Tuban. Keywords: Health Education, Healthy Home, Covid-19.